PROSES ENKULTURASI MANUSIA DALAM NOVEL AWAN KARYA SYAFRUDDIN PERNYATA - Diyan Kurniawati (Kantor Bahasa Provinsi Maluku Utara, 2020)
This research aims to reveal human’s enculturation process in an East Kalimantan novel Awan by Syafruddin Pernyata. It discusses about how the enculturation process carried out by the main character in this novel. It uses qualitative methods to analyze the enculturation process and the main character’s position in it. It applies the theory of literary sociology in order to examine the position of individuals in society and the forms of individual enculturation. Cultural identity is also portrayed to complement the analysis of the socio-cultural context among individuals. The analysis shows humans’ enculturation by traveling to the headstream of Mahakam river. That process of enculturation causes people to get survival strategies from the community living around the Semayang lake. A shift in understanding production is also occurring. Individuals understand that products can not only be produced in urban space, but also in the 2village. The analysis displays individuals that are involved and make cultural innovations after conducting the enculturation. The new culture is also supported by communication with the community as cultural agents. Conflicts with the community occur because old culture is a hereditary process. The novel of Awan shows that people experience the process of understanding and shifting the culture of their people. Keywords: human, culture, enculturation